Legitimizing Mataram’s Power Through the Islamization of Figures: A Case Study of the Babad Majapahit Text and the Wali (Sages) - Haryatmo, Sri; Pardi; Sudarmanto, Budi Agung (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The object of this study is the story of the birth of the character Kidang Telangkas (KT) in the Babad Majapahit and the Guardians (BMPW) which is linked to the story of the birth of Jaka Tarub (JT) in the Babad Tanah Jawi (BTJ). The purpose of this study is to reveal that there has been an Islamization of characters in the babad literature. The theory used is the theory of transformation. The method used is descriptive analytic. The result is that the text of the birth of KT in BMPW is a work of transformation of the story of the birth of Jaka Tarub (JT) in BTJ. This transformation causes several changes, especially changes in the name and identity of the character, the storyline, and the refinement of the character’s behavior. An interesting thing is that there is an "Islamization of the character", namely the change in the character’s identity from an ordinary human figure (the name Ki Jaka) to a figure of a cleric or bearer of Islamic teachings (the name Syekh Maulana Maghribi) who comes from the Arabian Peninsula. In addition, there is a change in the identity/social class of the character from an ordinary character (the name Sang Rara) to a noble character (Dewi Rasawulan). The Islamization of figures and the transformation of their identities in the BMPW (Islamic Religious Heritage Museum) were intended to legitimize the power of the Mataram kings through the compilation of genealogies. This occurred because these figures were believed to be the ancestors who gave rise to the Islamic Mataram dynasty/kings, as the Mataram Kingdom and its descendants adhered to Islam. This legitimacy effort was also carried out through the Islamization of these figures. In this regard, it is important to emphasize that Jaka Tarub is a central figure who serves as a mediator in the compilation of the genealogies and origins of the Islamic Mataram kings.